The METHODS OF INSTALLATION OF CONCRETE BLOCK LINING IN THE RANGE OF IRRIGATION MODERNIZATION PROJECT IN JATITUJUH DISTRICT MAJALENGKA DISTRICT - Sutisna, Laendra Anggara; Kholiq, Abdul (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
The Range Irrigation Area is a national strategic project located in the lowlands of the lower reaches of the Cimanuk River in the Northeastern part of West Java Province. Modernization of Span Irrigation is carried out because the age of the irrigation system is decades old, causing the performance of water services to decrease. The use of materials for construction that are in the ground or the groundwater table is by using a Steel Sheet Pile (SSP) which is driven to form a cofferdam (kisdam), this aims to provide a dry work area, and so that the river channel continues to flow from upstream to downstream, while the objective of the Irrigation Modernization is the coating/installation of concrete block lining in river channels so as to reduce the water loss factor. Concrete block lining is a precast concrete specially designed for irrigation canals which functions as a retaining wall. There are 9 stages of work regarding the Concrete Block Lining Installation Implementation Method, starting from Preparation, Coffering, Dewatering, Cut And Fill, Subgrade, Concrete Block Lining, Caping Beam, Joint Sealent/Filler and Tool Shifting. Kata Kunci : Modernization of Irrigation, Steel Sheet Pile (SSP), Concrete Block Lining.